2016
DOI: 10.1186/s12885-016-2693-3
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce invasion of human melanoma cells in vitro via differential regulation of N-cadherin expression and RhoA activity

Abstract: BackgroundHistone deacetylase inhibitors (HDACi) exert multiple cytotoxic actions on cancer cells. Currently, different synthetic HDACi are in clinical use or clinical trials; nevertheless, since both pro-invasive and anti-invasive activities have been described, there is some controversy about the effect of HDACi on melanoma cells.MethodsMatrigel and Collagen invasion assays were performed to evaluate the effect of several HDACi (Butyrate, Trichostatin A, Valproic acid and Vorinostat) on two human melanoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
5
15
0
Order By: Relevance
“…Detailed analysis of the effects of SAHA-loaded nanoparticles on EMT transition markers revealed a signi cant upregulated E-cadherin expression, but with no affect N-cadherin expression. This is consistent with previous studies, where HDACi were shown to have only a slight effect on N-cadherin expression in HT-144 and A375 cells [58]. E-cadherins mediate intercellular adhesion through the interaction of the extracellular and cytoplasmic domains with β-catenin.…”
Section: Discussionsupporting
confidence: 93%
“…Detailed analysis of the effects of SAHA-loaded nanoparticles on EMT transition markers revealed a signi cant upregulated E-cadherin expression, but with no affect N-cadherin expression. This is consistent with previous studies, where HDACi were shown to have only a slight effect on N-cadherin expression in HT-144 and A375 cells [58]. E-cadherins mediate intercellular adhesion through the interaction of the extracellular and cytoplasmic domains with β-catenin.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that RhoA and Rac1 were also regulated by histone deacetylase. (49)(50)(51) In this case, it is hard to prove the overall hypothetical mechanism that overexpression of SchLAH could downregulate RhoA and Rac1 by TSA treatment. However, mechanisms of SchLAH downregulation in HCC needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…SUR cell spheroids treated with HDAC inhibitors may exhibit invasive behaviour, with morphology suggestive of an invasive phenotype. It has been previously demonstrated that several HDAC inhibitors, such as SAHA, TSA, valproic acid and sodium butyrate, promote melanoma cell invasion in vitro via the upregulation of N-cadherin and inhibition of Ras homolog A activity (34). Using flow cytometry, it was found that parental and SUR cell spheroids treated with MGCD0103 alone or in combination with PLX4032 for 72 h had significantly reduced viability, whereas PLX4032 treatment alone did not lead to significant loss of viability (Fig S4D; Fig.…”
Section: Sensitivity Of Sur Cells To Epigenetic Inhibitorsmentioning
confidence: 99%